Block-Copolymer-derived plasmonic templates and its applications - Akinoglu, Gökalp Engin (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Plasmonic metasurfaces have important applications in life science, optics, and catalysis. However, their industrial usage is limited by high throughput nanofabrication. A promising solution is the transfer of a pattern into a substrate using block copolymers, nanostructured stamps or molds to create binary, three dimensional templates, which can then be decorated with plasmon active metals. Here, the optical properties of quasi-Babinet complementary arrays in the non-retarded regime is investigated by finite-difference time-domain simulations. The structures consist of a nanopillar support, which is covered with metal disks on top of the pillars and a quasi-Babinet complementary perforated film consisting of a hexagonal arranged hole array at the base of the pillars. Strong vertical plasmonic coupling occurs for small separation distances of the plasmonic slabs. The thesis presents a comprehensive study of the near and far-field properties of such vertically coupled plasmonic arrays varying their geometric dimension and the employed metals with their intrinsic plasmonic material properties. In particular, gold, silver, copper, aluminum, nickel, and palladium are considered. Furthermore, the effect of the refractive index of the nano-pillar support is investigated. The plasmonic slabs show tunable extraordinary transmission and large electric near-field enhancements, which is strongly dependent on the employed material and geometry. Further, it is shown that the templates are suitable for plasmonic hetero-structures commonly used in plasmon-enhanced photocatalysis. Finally, the thesis reports on a block copolymer derived vertically coupled plasmonic template for surface enhanced Raman spectroscopy. Nanopillar templates were fabricated by the incorporation of an iron salt precursor into a self-assembled block copolymer thin film and subsequent reactive ion etching. Subsequently, the nanopillars were coated with gold to create quasi Babinet complementary plasmonic templates. An increase of surface enhanced Raman scattering efficiency for smaller pillar heights and stronger coupling between the dot array and perforated gold film with average enhancement factors as high as 107 is observed. In addition, the block copolymer derived templates show an excellent relative standard deviation of the Raman intensity up to 8%.
APPROVED
Keywords: Block copolymer lithography; Nanopillar; FDTD simulation; Plasmonics; SERS